Women in Business - Cesaroni , Francesca Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
[The role of women in entrepreneurship, management and corporate governance is regarded as central to the development and welfare of economies. Since the early 1980s, there has been increased interest in women managers and entrepreneurs, often from an interdisciplinary approach, combining, for example, sociology, psychology, management and organisational studies and economics. Nowadays, research on women in management and organisations is continuously and rapidly evolving (Paoloni and Demartini, 2016). Research on how women face new business challenges within organisations-as entrepreneurs, owners, managers, as well as workers-can contribute to understanding the new drivers affecting value creation dynamics in our knowledge-based society (Cesaroni, Demartini and Paoloni, 2017). Accordingly, this book tries to offer some insights on how women create, process and share knowledge in their business activity through the application and exploitation of novel creative ideas and solutions]